Localized relaxation's strength and its mimicry of glass-softening thermodynamics. - VIJ, JAGDISH KUMAR (American Institute of Physics, 2002)
The dielectric relaxation strength of the ? process, ???, in a rigid-molecular glass of 16.6 mol?% chlorobenzene cis-decalin mixture increases slowly with temperature, T, until the glass-softening range is reached, and thereafter it increases rapidly, i.e., (d???/dT) increases at Tg relatively abruptly. This is remarkably similar to the volume and entropy against T plots of a glass being heated through its Tg and of the implied rise in the expansion coefficient and heat capacity near Tg. The ?-relaxation rate increases smoothly through Tg according to the Arrhenius equation, and the distribution of relaxation times becomes narrower. Both the entropy and free volume affect ???, but not the rate
PUBLISHED
Keywords: Electronic & Electrical Engineering